SMEs foreign establishment decision-making: A multiple-case research of internationalisation strategies in the metallurgy and metal-mechanic industry - Abrantes, B. F.; Preto, M. T.; António, N. (International Journal of Management and Decision Making, 2020)
This research aims to untangle the decision-making of Portuguese firms in their selection of overseas host-markets. Herein, a theoretical review will cover both the decision-making and internationalisation theory. Restricted to a target population of SMEs, the empirical testing is focused on the areas of risk-perception and the pace of commitment, and is therefore, a multiple case design comprising a representative sample of the different segments of the sector. The research follows a post-positivistic rationale aligned with its descriptive-evaluative purpose, combining the collection of contrived data and subsequent manipulation in a sequential explanatory mixed methods logic. Quantitative data from documentary analysis, is proceeded by qualitative data from interviews to the strategic apex of the case-firms, coded through content analysis. Results demonstrate that commitment decisions follow distinctive risk-profiles, influenced by a dyad of Ricardian comparative-advantage factors and public policy’ practices impacting directly on cross-border establishment decisions.